Induction of Apoptosis by Metabolites of Rhei Radix et Rhizoma (Da Huang): A Review of the Potential Mechanism in Hepatocellular Carcinoma - Jiang, Huanyu; Tang, Wuyinuo; Song, Yang; Jin, Wei; Du, Quanyu (Frontiers in Pharmacology, 2022)
Liver cancer is a global disease with a high mortality rate and limited treatment options. Alternations in apoptosis of tumor cells and immune cells have become an important method for detailing the underlying mechanisms of hepatocellular carcinoma (HCC). Bcl-2 family, Caspase family, Fas and other apoptosis-related proteins have also become antagonistic targets of HCC. Da Huang (Rhei Radix et Rhizoma, RR), a traditional Chinese herb, has recently demonstrated antitumor behaviors. Multiple active metabolites of RR, including emodin, rhein, physcion, aloe-emodin, gallic acid, and resveratrol, can successfully induce apoptosis and inhibit HCC. However, the underlying mechanisms of these metabolites inhibiting the occurrence and development of HCC by inducing apoptosis is complicated owing to the multi-target and multi-pathway characteristics of traditional Chinese herbs. Accordingly, this article reviews the pathways of apoptosis, the relationship between HCC and apoptosis, the role and mechanism of apoptosis induced by mitochondrial endoplasmic reticulum pathway and death receptor pathway in HCC and the mechanism of six RR metabolites